EVALUATION OF THE IMPACT OF MADRASAH YOUNG TEACHER FUNCTIONAL TECHNICAL TRAINING PROGRAM - Yasri Yasri; Burhanuddin Tola (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
This study aims to evaluate the impact of the Technical Functional Teacher Training Program Madrasah held by the Technical Center of Ministry of Religious Affairs. This study used modified Kirkpatrick level Result model and case study method. The study was conducted in 58 Madrasahs with 518 respondents consisting of alumni of trainees, colleagues, and head of Madrasah. Technique of collecting data by way of questionnaire, observation and interview. Data processing is done by quantitative and qualitative descriptive technique. The results of this study show that the training alumni are able to arrange the tools and carry out the process and assessment of learning, ensuring the quality of planning, completing routine work, solving problems, improving working relationships and cooperation, implementing the results of the training, receiving and advising. But alumnus do not use ICT in learning, do not do reflective action, do not implement knowledge and skill in work. This capability is not entirely the result of the role of Technical Training Center of the Ministry of Religious Affairs. Keywords: impact evaluation, training program, alumni performance, and work unit performance